TET2, ASXL1, IDH1, and IDH2 Single Nucleotide Polymorphisms in Turkish Patients with Chronic Myeloproliferative Neoplasms - Nur Soyer; Burçin Tezcanlı Kaymaz; Melda Cömert Özkan; Çağdaş Aktan; Ali Şahin Küçükaslan; Fahri Şahin; Buket Kosova; Güray Saydam (Turkish Journal of Hematology, 2017)
We aimed to determine the genotype distribution, allele frequency, and prognostic impact of IDH1/2, TET2, and ASXL1 single nucleotide polymorphisms (SNPs) in myeloproliferative neoplasms (MPNs). TET2 (rs763480), ASXL1 (rs2208131), and IDH1 (rs11554137) variant homozygous genotype frequencies were found at rates of 1.5%, 9.2%, and 2.3%, respectively. No IDH2 SNP was identified. IDH1 and TET2 frequencies were 5% in essential thrombocythemia (ET) and 1.7% in ET and 5% in primary myelofibrosis (PMF), respectively. ASXL1 frequencies were 8.3%-10% in MPN subgroups. The TET2 mutant allele T and ASXL1 mutant allele G had the highest frequencies with 0.272 in the PMF and 0.322 in the polycythemia vera (PV) group, respectively. There was no impact of the SNPs on prognosis. IDH1 frequency in MPNs was found similar to the literature. ASXL1 frequencies were similar between ET, PV, and PMF patients. The ASXL1 and TET2 allele frequencies of the Turkish population are similar to those of the European population. The role of SNPs in MPNs might be further evaluated in larger multicenter studies.